A generic method to synthesise graphitic carbon coated nanoparticles in large scale and their derivative polymer nanocomposites - Wang, Nannan; Yang, Zhuxian; Xu, Fang; Thummavichai, Kunyapat; Chen, Hongmei; Xia, Yongde; Zhu, Yanqiu (Nature Publishing Group, 2017)
A versatile Rotary Chemical Vapour Deposition (RCVD) technique for the in-situ synthesis of large scale carbon-coated non-magnetic metal oxide nanoparticles (NPs) is presented, and a controllable coating thickness varying between 1–5 nm has been achieved. The technique has significantly up-scaled the traditional chemical vapour deposition (CVD) production for NPs from mg level to 10 s of grams per batch, with the potential for continuous manufacturing. The resulting smooth and uniform C-coatings sheathing the inner core metal oxide NPs are made of well-crystallised graphitic layers, as confirmed by electron microscopy imaging, electron dispersive spectrum elemental line scan, X-ray powder diffractions and Raman spectroscopy. Using nylon 12 as an example matrix, we further demonstrate that the inclusion of C-coated composite NPs into the matrix improves the thermal conductivity, from 0.205 W∙m−1∙K−1 for neat nylon 12 to 0.305 W∙m−1∙K−1 for a 4 wt% C-coated ZnO composite, in addition to a 27% improvement in tensile strength at 2 wt% addition.